2023
DOI: 10.1093/toxsci/kfad001
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic causes distinct gene expression changes in macrophages polarizedin vitrowith either interferon-γ or interleukin-4

Abstract: Arsenic exposure is correlated with atherosclerosis in epidemiological studies and in animal models. We have previously shown that arsenic exposure enhanced atherosclerotic plaque size, increased plaque lipid content and decreased plaque smooth muscle cell and collagen contents in apoE-/- mice. However, the percentage of plaque-resident macrophages, the primary drivers of atherosclerosis remained unchanged. Therefore, we hypothesized that while arsenic does not change the quantity of macrophages, it alters mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 81 publications
1
3
0
Order By: Relevance
“…Intriguingly, the increased granularity provided by scRNASeq demonstrated that arsenic alters the transcriptome of the resident-like and foam-like macrophages uniquely. Supporting this conclusion, previous in vitro data from our lab demonstrated that arsenic resulted in distinct gene expression changes depending upon whether IFN-ɣ or IL-4 was used to polarize macrophages (20). This is intriguing as macrophages typically respond to their microenvironment and adopt a polarized functional state to respond to stimuli (51).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Intriguingly, the increased granularity provided by scRNASeq demonstrated that arsenic alters the transcriptome of the resident-like and foam-like macrophages uniquely. Supporting this conclusion, previous in vitro data from our lab demonstrated that arsenic resulted in distinct gene expression changes depending upon whether IFN-ɣ or IL-4 was used to polarize macrophages (20). This is intriguing as macrophages typically respond to their microenvironment and adopt a polarized functional state to respond to stimuli (51).…”
Section: Discussionsupporting
confidence: 62%
“…Atherosclerotic plaques are complex microenvironments and recapitulating them in vitro is challenging. Therefore, we utilized data from our previously published bulk RNA-Seq comparison of IFN-ɣ or IL-4-activated bone marrow-derived macrophages with or without concomitant arsenic exposure (Figure 6G and Tables S16-S19) (20). Based on the expression of target genes, STAT6 is the only transcription factor significantly altered in IFN-ɣ -polarized macrophages (p-value: 3.63e-2), and the only transcription factor common between the two in vitro-acquired macrophages and the in vivo single cell sequencing datasets (p-value: 1.2e-3) (Figure 6H and Table S20).…”
Section: In Vitro Validation Of In Vivo Single Cell Datasetsmentioning
confidence: 99%
See 2 more Smart Citations